Successful use of recombinant activated factor VII for postoperative associated haemorrhage: a case report - Vlachos, Konstantinos (BioMed Central, 2008)
BACKGROUND: Coagulopathy is a major contributing factor to bleeding related mortality even after achieving adequate surgical control of the haemorrhage in trauma and surgical patients. CASE PRESENTATION: A 65 years old Greek man was admitted in our ICU with critical haemorrhage following renal biopsy. Despite surgical exploration the patient continued to bleed resulting in a vicious cycle of transfusion, coagulopathy and re-bleeding. After all standard management options were exhausted, the patient was given rFVIIa (total dose 4,8 mg). Clinical improvement was noted without adverse thrombotic complications. One month later the same patient was operated on for a suspected retroperitoneal infected collection that it was assumed to be the cause of persistent pyrexia. After abdominal washout, he suffered haemorrhagic shock with postoperative coagulopathy. Standard transfusion therapy was again unsuccessful. The patient was given rFVIIa again resulting in an immediate reduction in coagulopathic haemorrhage accompanied by a significant improvement in laboratory measurements and reduction in blood products requirements. CONCLUSION: Published clinical experiences for the use of rFVIIa in trauma patients are limited to small series and case reports. However, in trauma patients, administration of rFVIIa appears to be effective in addition to prompt surgical intervention as an adjunctive haemostatic measure to control life threatening bleeding in appropriately selected patients.